Efektivitas Pelayanan Pembuatan Surat Izin Mengemudi (SIM) Menuju Era Digitalisasi di Kepolisian Resor Jayapura Kota - Lina Andayani; Peliman Ndibau; Sahriani Sahriani; Syamsudin Syamsudin (Jayapangus Press, 2026)
Public service is a fundamental manifestation of the state apparatus function in serving the community. Amid digital transformation, the Police must provide faster, more accessible, and transparent services. This study analyzes the effectiveness of driver's license (SIM) issuance services at the Jayapura City Resort Police (Polresta), focusing on the Digital Korlantas Polri application (SINAR/SIM Nasional Presisi). Rapid growth in vehicle ownership has heightened demand for SIM services, amid persistent illicit practices such as